DAMPAK TAMAN WISATA PUNCAK TERHADAP PERTUMBUHAN PENDAPATAN MASYARAKAT DI DESA BILA RIASE KECAMATAN PITU RIASE KABUPATEN SIDENRENG RAPPANG - Darmana, Dady; Rahman, Zainuddin; Mapparenta, Mapparenta; Alamsyah, Alamsyah (Economos : Jurnal Ekonomi dan Bisnis, 2021)
Regional tourism is one of the components of the economy that can be developed as a source of regional income and the income of the surrounding community in particular. The aims of conducting this research are 1) to find out whether the number of tourist visits affects community income; 2) to find out whether the tourist stay time affects community income; 3) to find out whether the number of rides has an impact on the growth of community income. The data used in this research was qualitative data obtained from respondents by conducting interviews, then it processed through data tabulation to see the comparison of each opinion and information given by respondents related to the research problem. The results of this research indicated that the number of tourists visits affects the income of the surrounding community who are the owners of Small and Medium Enterprises as well as stay time duration and the number of rides. Generally, the peak tourism park has succeeded in encouraging and influencing the economy of the surrounding community through employment and the creation of business opportunities.Â  Concerning the research results that found the peak tourist park made a major contribution in encouraging the economy of the surrounding community, the government should pay more attention to the development of tourism in Sidenreng Rappang Regency in the future.